Mortality and Epidemiological Transition of the Lithuanian Population in 1849–1921 - Bugienė, Dovilė (Sociologija. Mintis ir veiksmas, 2021)
With the modernization of societies, mortality is one of the key factors in the process of population change. Mortality since the middle of the 20th century in Lithuania has been widely studied in various aspects. However, the previous historical period in this field is still little studied and data on the changes in the development of Lithuanian mortality are almost unavailable. This article presents a study on the basis of the information from Roman Catholic churches death records books to reconstruct the structure of causes of death in the Lithuanian population in 1849–1921, its differences between urban and rural areas, and the links with A. R. Omran’s theory of epidemiological transition. The data of death records suggests the epidemiological transition in Lithuania began at the end of the 19th century – the beginning of the 20th century and displays the influence of the type of place of residence on the pace of mortality change.
Keywords: epidemiological transition; demography; causes of death; mortality; parish registers; death records